The Role of Coresidency with Adult Children in the Labor Force Participation Decisions of Older Men and Women in China - Rachel Connelly; Margaret Maurer-Fazio; Dandan Zhang (Institute for the Study of Labor (IZA), 2014)
Over the course of China's economic reforms, a pronounced divergence in the labor force participation patterns of rural and urban elders emerged – rural elders increased their rates of participation while urban elders reduced theirs. In this project, based on the data of the Chinese population censuses of 1982 and 2000, we employ a two-stage procedure to take into account the endogeneity of the residency and labor force participation decisions of older persons. We find that the effect of coresidency with adult children on the labor force participation of older adult differs by urban vs. rural residence. In 1982, the LFPR of urban elders who coresided with their adult children were significantly higher than those who did not coreside. By 2000, this effect completely disappeared. In contrast, in rural areas, coresidency with adult children had a large and significant negative effect on the labor force participation of both male and female elders. This effect diminished only slightly over the reform period. Finally, we decompose the changes over time in elders' labor force participation decisions and find that the response effect for all groups (male and female, urban and rural) is positive, such that, holding the levels of demographic and economic variables constant, each group of elders would have had higher rates of participation in 2000 than in 1982. The remarkable divergence in urban and rural elders' labor force participation trends are due to differences in the relative sizes of their attribute and response effects.
Keywords: J14; J26; J11; J12; J13; J16; J22; O15; O53; P23; R23; 330; labor force participation; elders; China; retirement; coresidency; rural and urban; living arrangements